REALITAS SIMBOL KEISLAMAN DALAM FILM TELEVISI ISLAMIC SYMBOLIZATION REALITY ON TELEVISION FILM - Hermawan, Herry (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
This research  is  concerned  to present  an analysis   of Islamic  symbolization    in the context  of a theory  of social  construction   of reality  as a dialectical  process consist    of    three    moments    or    step,     externalization.     objectification     and internalization.      Through    the    qualitative     research     method.     the   analysis techniques   in  use  were genre   and  narrative   analysis,   semiotics   analysis  and hermeneutics    analysis.     The   result   of   this   research    showed    that   Islamic symbolization   reality  whether  it is constructed   by society  or liy television film derive from  the paramount  realities  of interaction   between religion.  culture  and economy.   The  result  of  research   also  showed   that  capitalism   is  a  dominant ideologv  in which  stand  up behind  the text  of  Islamic  svmbolization   television film.